The impact of iron chelation therapy on patients with lower/intermediate IPSS MDS and the prognostic role of elevated serum ferritin in patients with MDS and AML: A meta-analysis - Yang, Yuan (Medicine (Baltimore), 2019)
Serum ferritin (SF) has been identified as a potential prognostic factor for patients undergoing stem cell transplantation, but the prognostic value of SF in acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS) patients and the impact of iron chelation therapy (ICT) on MDS patients are controversial. The present meta-analysis aimed to better elucidate these relationships. Three electronic databases were searched systematically to identify reports on the prognostic role of SF in MDS and AML patients, and those investigating the impact of ICT on prognosis of MDS patients. The hazard ratios (HRs) and its 95% confidence interval (95%CI) were extracted from the identified studies using Cox proportional hazard regression model for overall survival (OS) and progression of MDS to AML. Twenty reports including 1066 AML patients and 4054 MDS patients were included in present study. The overall pooled HRs for OS of AML and MDS patients with elevated SF prior to transplantation was 1.73 (1.40–2.14), subgroup analyses stratified by the cut-off value of SF ≥1400/1000 ng/mL showed that the pooled HRs were 1.45 (0.98–2.15) and 1.65 (1.30–2.10), respectively. The pooled HRs for ICT in MDS patients was 0.30 (0.23–0.40). For ICT, the pooled HRs for the progression of MDS to AML was 0.84 (0.61–1.61). SF has a negative impact on the OS of AML and MDS patients when it is higher than 1000 ng/mL. ICT can improve the OS of MDS patients with iron overload but it is not associated with the progression of MDS to AML.